ACTIVITIES OF THE UNIVERSITY FOR INVOLVEMENT STUDENTS TO THE WORLD OF MATHEMATICS KNOWLEDGE - Aitek Koichuev; Adra Mamchuev (Вестник Северо-Кавказского федерального университета)
The article describes the experience of the University of informal activities to develop interest of students to the mathematical disciplines. Marked mechanisms to identify and engage in scientific research mathematically gifted young people, including summer school, the annual competitions of educational and scientific and research works of students and young scientists. Showing professional orientation and socioeconomic importance of research projects, some of the conditions and characteristics of the functioning of the forum in the field of mathematics education.